STUDI EMPIRIK TENTANG PENINGKATAN PENDAPATAN ASLI DAERAH SEBAGAI RANCANGAN UNDANG-UNDANG - M. Kuswantoro (Jurnal Ekonomi-Qu, 2018)
ABSTRACTThe aim of this research is to analyze the implementation of local revenue management and the implementation of local revenue arrangement according to the legislation in Banten Province. Research data are collected from any literature reviews, research results, and interview with some stockholders and scholars. The research result show that Banten Province has largepotency of local revenue. However, there are some weaknesses on the implementation, particularly the allocation fund for planning requirement could not be met.